Neurosains Lingkungan Belajar: Tinjauan Sistematis Tentang Aktivitas Otak Dan Motivasi Siswa Dalam Konteks Pendidikan - Bahran; Muhammad Al Azhar; Nailul Muna; Kharisma Yuliana; Riza Nurlaili M; M. Reza H; Bagus Mahardika (Jurnal Ilmu Pendidikan, 2025)
The development of neuroscience makes a significant contribution to the world of education, especially in understanding how students' brains work and respond to the learning environment. Learning environments that include physical, social, and pedagogical aspects have been shown to influence brain activity as well as student learning motivation. This study aims to systematically examine the relationship between neuroscience, learning environment, brain activity, and student learning motivation in the context of education. The research method used is library research by examining various primary and secondary sources in the form of scientific journals and relevant books. Data analysis techniques are carried out qualitatively through text and discourse analysis with an inductive approach and theoretical triangulation to maintain the validity of the data. The results of the study show that neuroscience-based classroom management, positive social interaction between teachers and students as well as between students, and the implementation of learning strategies that are in accordance with how the brain works can improve cognitive activity, emotion regulation, and intrinsic motivation of students. However, the application of neuroscience in learning still faces various challenges, such as limited teacher understanding, lack of training, and not being optimally integrated neuroscience in the curriculum. Therefore, continuous efforts are needed to improve teacher competence and the development of neuroscience-based learning models so that the learning process becomes more effective and meaningful.